High-quality genome sequence and description of Paenibacillus dakarensis sp. nov. (March 2016) - Lo, C.I.; Sankar, S.A.; Fall, B.; Sambe-Ba, B.; Mediannikov, O.; Robert, C.; Faye, N.; Wade, B.; Raoult, D.; Fournier, P.-E.; Fenollar, F.
Abstract: Strain FF9T was isolated in Dakar (Senegal) from a blood-culture taken from a 16-month-old child. MALDI-TOF analysis did not allow for identification. After sequencing, strain FF9T exhibited 98.18% similarity with the 16SrRNA sequence of Paenibacillus uliginis. A polyphasic study of phenotypic and genomic analyses showed that strain FF9T is Gram variable, catalase-positive, and presents a genome of 4, 569, 428 bp (one chromosome but no plasmid) with 4, 427genes (4, 352 protein-coding and 75 RNA genes (including 3 rRNA operons). The G+C content is 45.7%. On the basis of these genomic and phenotypic data analyses, we propose the creation of Paenibacillus dakarensis strain FF9T.